Direct measurement of the mass difference between top and antitop quarks - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Zielinski, M.; et al. (Amer Physical Soc, 2011)
We present a direct measurement of the mass difference between top and antitop quarks (Delta m) in lepton + jets t (t) over bar final states using the matrix element method. The purity of the lepton + jets sample is enhanced for t (t) over bar events by identifying at least one of the jets as originating from a b quark. The analyzed data correspond to 3.6 fb(-1) of p (p) over bar collisions at root s = 1.96 TeV acquired by D0 in Run II of the Fermilab Tevatron Collider. The combination of the e + jets and mu + jets channels yields Delta m = 0.8 +/- 1.8(stat) +/- 0.5(syst) GeV, which is in agreement with the standard model expectation of no mass difference.